2011
DOI: 10.1128/jb.00198-11
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Diffusive Motion of RNA Polymerase in Live Escherichia coli

Abstract: By labeling the ␤ subunit of RNA polymerase (RNAP), we used fluorescence microscopy to study the spatial distribution and diffusive motion of RNAP in live Escherichia coli cells for the first time. With a 40-ms time resolution, the spatial distribution exhibits two or three narrow peaks of 300-to 600-nm full width at half-maximum that maintain their positions within 60 nm over 1 s. The intensity in these features is 20 to 30% of the total. Fluorescence recovery after photobleaching (FRAP) measures the diffusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 35 publications
6
44
0
Order By: Relevance
“…This analysis showed that ∼48% of RNAPs were bound and ∼52% were mobile (Fig. 1B, Inset); this result is in agreement with previous estimates from both fluorescence recovery after photobleaching (26) and single-molecule tracking (23). We then determined a D* threshold (0.16 μm 2 /s) which preserves the bound-to-mobile ratio, and allows sorting of individual trajectories as corresponding to bound or mobile RNAP molecules (SI Materials and Methods).…”
Section: Significancesupporting
confidence: 88%
“…This analysis showed that ∼48% of RNAPs were bound and ∼52% were mobile (Fig. 1B, Inset); this result is in agreement with previous estimates from both fluorescence recovery after photobleaching (26) and single-molecule tracking (23). We then determined a D* threshold (0.16 μm 2 /s) which preserves the bound-to-mobile ratio, and allows sorting of individual trajectories as corresponding to bound or mobile RNAP molecules (SI Materials and Methods).…”
Section: Significancesupporting
confidence: 88%
“…To determine whether the DksA cross-link was to b or b9, we repeated the reaction with each of the six DksA-Bpa proteins and RNAP containing a b9 subunit with a C-terminal GFP fusion adding ;27 kDa to b9 (Bratton et al 2011). In all six cases, ;90%-95% of the radiolabeled cross-linked species migrated slightly slower than with wild-type RNAP to a position consistent with the molecular weight (MW) of a complex containing b9-GFP (155 kDa plus 27 kDa) cross-linked to DksA (18 kDa) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, to address the effect of crowding on the initiation of transcription, we first need to estimate whether this reaction is diffusion-limited. For a large protein complex such as RNA polymerase, the cytoplasmic diffusion coefficient is approximately 1 µm 2 /s [28,48], which is reduced due to non-specific binding to approximately 0.2 µm 2 /s [48,49]. Thus, the diffusion-limited binding rate to a promoter can be estimated to be about 0.1 µM −1 s −1 .…”
Section: Transcriptionmentioning
confidence: 91%